Dental Arch Relationships in Turkish Patients with Complete Unilateral Cleft Lip and Palate Born between 1976 and 1990: A Comparison with Eurocleft. (January 2014) - Dogan, Servet; Semb, Gunvor; Erbay, Elif; Alcan, Toros; Uzel, Ash; Kocadereli, Ilken; Shaw, William C.
Objective: To compare the dental arch relationships of Turkish patients with complete unilateral cleft lip and palate (UCLP) with the results reported for participants in the Eurocleft study. Patients: Study models of 109 patients with complete UCLP from five university clinics in Turkey were evaluated (clinic A = 25 patients, clinic B = 23 patients, clinic C = 20 patients, clinic D = 21 patients, and clinic E = 20 patients). The mean age of the patient cohort was nine years old (range = 8–11 years old), and the cohort was born between 1976 and 1990. Methods: The examiners rated the three-dimensional (3D) models using the GOSLON Yardstick. The scores were compared with those from the Eurocleft centers: E1(B), E2(E), E3(A), E4(F), E5(C), and E6(D). Intra- and interexaminer agreements were evaluated using weighted kappa statistics. Results: The mean GOSLON scores for the Turkish clinics were as follows: clinic A = 3.16, clinic B = 3.13, clinic C = 3.25, clinic D = 3.67, and clinic E = 3.70. Scores for three of the Turkish clinics (A, B, and C) were significantly worse than the scores for the three best Eurocleft centers, E1(B), E2(E), and E3(A) ( P < .001, P < .001, and P < .05, respectively). Scores for two of the Turkish clinics (D and E) were similar to those for Eurocleft center E6(D) but worse than the scores for the other Eurocleft centers ( P < .01, P < .001, respectively). Conclusions: This was the first study in which three-dimensional models were used to derive scores to compare with those of the Eurocleft centers. According to the results of analysis of 109 3D models, 50.4 % of the patients in Turkey were classified as GOSLON score 4 and 5. This may have been attributable to poor surgical procedures, low-volume surgeons, and the decentralized treatment approach in Turkey between 1985 and 2000. Further research is needed to assess the situation in Turkey in more recent years.